Understanding the contribution of operator measurement variability within Flow Cytometry data analysis for Quality Control of Cell and Gene Therapy manufacturing. (January 2020) - Grant, Rebecca; Coopman, Karen; Medcalf, Nicholas; Silva-Gomes, Sandro; Campbell, Jonathan J.; Kara, Bo; Braybrook, Julian; Petzing, Jon
Highlights: There is up to a 92% reduction in variation when operators follow prescribed protocols for analysis. Different control limits must be validated to ensure outliers are understood. Log transforms, when applied to 'normalise' data, can change the outliers defined by control limits. Abstract: Flow Cytometry is a measurement technique used in Quality Control and in-process measurements of biomanufactured Cell and Gene Therapy products. However, it contains a number of sources of measurement variation at; sample preparation, instrument setup, analysis, and post-analytical data analysis stages. The latter sees variation introduced from operator subjectivity, which is investigated here to understand what effects the interpretation of diagrammatical protocols have on inter-operator analysis. 36 operators from different sites were given a series of histograms to analyse, gating a shifting peak. This was repeated with diagrammatical protocols to apply gates which reduced inter-operator variation by up to 92%. Various control limits include and exclude different results and when adjusted with a log transform differences in outlier discrimination have been found. This research supports the use of Flow Cytometry diagrammatical protocols to reduce the contribution of inter-operator variation and measurement uncertainty associated within Cell and Gene Therapy manufacturing scenarios.